Addendum: A FRET biosensor for necroptosis uncovers two different modes of the release of DAMPs - Shin Murai (Nature Portfolio, 2019)
The cDNA sequence of human SMART described in this Article was misreported, as described in the accompanying Addendum. This error does not affect the results or any conclusion of the Article.